Review Findings of Drug-induced Sleep Endoscopy (DISE) in Children with Obstructive Sleep Apnea (OSA) - Gerry Man-Fung Yeung; Shuk-Yu Leung; Ka-Li Kwok (Pediatric Respirology and Critical Care Medicine)
Background: Drug-induced sleep endoscopy (DISE) is an objective assessment and diagnostic procedure of the upper airway obstruction (UAO) under sedation. Findings of DISE in Hong Kong pediatric group patients with obstructive sleep apnea (OSA) are limited. Materials and Methods: This is a single-center retrospective chart review study on DISE findings in pediatric patients with OSA documented by polysomnography (PSG). We used the DISE scoring system proposed by Chan 2014, Fishman 2013 together as our internal practice. A standard sedation protocol was conducted. Endoscopic findings were recorded and evaluated the level of obstruction, severity, and correlation with PSG parameters. Results: A total of 124 patients who underwent DISE were reviewed in our study. Multiple levels of obstruction had been observed in all patients. Forty-five (36.6%) patients suffered from severe obstruction in more than one level. Tongue base was the most common level being severely obstructed. DISE total score is positively correlated with obstructive apnea-hypopnea index (oAHI, r = 0.35, P = <0.001), negatively correlated with oxygen nadir (SpO2 nadir, r = –0.32, P = <0.001), and positively correlated with desaturation index (DI, r = 0.34, P < 0.001). In the subgroup analysis of the post-adenotonsillectomy (AT) group, scores in nostrils, tongue base, and supraglottic showed significantly increased. None of the subjects had complications from sedation or the endoscopy procedure. Conclusion: In our study, DISE was shown to be a safe, feasible, and informative assessment tool for pediatric OSA patients. In particular, multiple levels of obstruction were common in children and we observed a significant correlation between the severity of UAO measured by DISE in children with OSA and PSG parameters. Changes in UAO sites were observed when preoperative patients underwent surgical treatment.